IN THE CONDITIONS OF THE KHOREZM REGION, THE SPREAD OF TERMITES AND MEASURES TO COMBAT THEM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In the Khorezm region, the spread of termites has become a significant concern, especially in areas where agriculture and construction activities are critical. Termites, particularly subterranean species, cause severe damage to buildings and crops, leading to economic losses. This article explores the ecological conditions that favor termite proliferation in Khorezm, reviews scientific literature on termite control, and outlines both traditional and modern methods for combating these pests. Recommendations are provided to enhance integrated pest management in the region.